What school nurses receive for themselves that influences their remaining in practice: A qualitative study - Linda Horne Mæland; Bjørg Frøysland Oftedal; Margareth Kristoffersen (BMC, 2023)
Abstract Background Previous research indicates a link between what nurses receive for themselves and their remaining in practice. In Norway, school nurses tend to remain in practice, but what it is they receive for themselves has been scarcely studied. The aim of this study, therefore, was to describe and interpret what it is school nurses receive for themselves that influences their remaining in practice. Method The study has a qualitative design with a hermeneutic approach. Data were collected through individual interviews on two separate occasions with 15 Norwegian school nurses. The data were analysed using a phenomenological hermeneutic method. Results Two themes demonstrate what it is the school nurses receive for themselves: (1) 'Gaining interesting workdays for yourself' and (2) 'Attaining pleasure for yourself'. Each theme has two sub-themes. The first theme involved the school nurses 'having an attractive scope of practice' and 'having varied tasks'. The second theme involved 'being trusted' and 'being given a response'. The study themes can be comprehensively understood as an expression of what the school nurses identify as the main locus of the good work-life. The school nurses' remaining seems to revolve around what it is they receive on their own behalf: an affirmation for their ordinary life and what they do as a nurse. Conclusion This study highlights that what school nurses receive on their own behalf may influence their remaining in practice. It adds to previous research with a more specific understanding of nurses remaining in practice by stating that in identifying the main locus of the good work-life, the school nurses received affirmation for their ordinary life and what they do as a nurse. Thus, it is important that nurses identify the main locus of a good work-life for themselves, as receiving affirmation for what they do in their ordinary workdays may influence their remaining in practice. Registration of clinical trial and registration identification number The study was approved by the Norwegian Centre for Research Data (project 59195). National Research Ethics Committee approval was not required, as the study only involved health professionals and did not ask for sensitive information.